Fall Movements of Belugas (Delphinapterus leucas) with Satellite-linked Transmitters in Lancaster Sound, Jones Sound, and Northern Baffin Bay - Richard, P.R.; Heide-Jørgensen, M.P.; St. Aubin, D. (ARCTIC, 1998)
Six adult belugas, Delphinapterus leucas, (2 males, 4 females) were instrumented with satellite-linked transmitters in Croker Bay, southeastern Devon Island in the Canadian High Arctic in mid-September 1995. Some days, the animals remained close to shore along the southeastern and eastern shoreline of Devon Island, presumably foraging for arctic cod (Boreogadus saida) and other prey. They spent the rest of the time in the deep waters of Lady Ann Strait, eastern Jones Sound, and the waters southeast of Coburg Island, presumably feeding on deepwater prey. Only males went farther north in water off southeastern Ellesmere Island, the belugas' swimming speeds decreased in the later part of the study period. Their last transmissions came from the North Water, an area where belugas are known to winter. Results of this study were not sufficient to determine the extent of movement of belugas between the eastern Canadian Arctic and Greenland. À la mi-septembre 1995, on a installé des émetteurs en liaison avec un satellite sur six bélugas adultes (Delphinapterus leucas) - 2 mâles, 4 femelles - dans la baie Croker, au sud-est de l'île Devon dans l'Extrême-Arctique canadien. Certains jours, les six bélugas se tenaient près de la côte sud-est et est de l'île Devon, probablement à la recherche de morue arctique (Boreogadus saida) ou d'autres proies. Ils ont passé le reste du temps dans les eaux profondes du détroit de Lady Ann, de l'est du détroit de Jones, et dans les eaux du sud-est de l'île Coburg, se nourrissant probablement de proies habitant les grands fonds. Seuls les mâles se sont rendus plus au nord dans les eaux au large du sud-est de l'île Ellesmere. La vitesse de nage des bélugas a diminué durant la dernière portion de l'étude. Les derniers signaux provenaient de l'Eau du Nord, une région où l'on sait que les bélugas passent l'hiver. Les résultats de cette étude sont insuffisants pour évaluer l'ampleur des déplacements de bélugas entre l'est de l'Arctique canadien et le Groenland.